Study of heat and mass transfer during drying process of maize grain pile based on computed tomography - Ge, Mengmeng; Chen, Guixiang; Liu, Wenlei; Liu, Chaosai (Biosystems engineering, 2024)
A detailed model for heat and moisture dynamics within the maize piles drying is created to investigate thermal and moisture transfer, specifically using maize as the subject of research. 3D reconstructions of maize piles using image processing methods and computed tomography technology enabled accurate geometric modelling. The drying process was analysed using finite element simulations, validated through maize drying experiments. An investigation into how airflow rate, thermal conditions, and moisture levels affect the drying behaviours was conducted. This study revealed that velocity decreases incrementally from the core towards the edges of the pores. Along the direction of the airflow, pressure and temperature both continuously reduce, showing a clear stratification effect. The complex airflow distribution within grain piles leads to uneven temperature distribution in maize piles. Higher ventilation speeds enhance heat transfer within the maize pile, accelerating the temperature rise of the kernels. Heat transfer takes place at a much quicker rate than moisture transfer. The drying duration is primarily determined by moisture transfer rather than heat transfer. In contrast to heat transfer, moisture diffusion within the grain pile requires significantly more drying time. Increasing the temperature of the ventilating air can intensify heat transfer between the kernels and the air, while also promoting moisture diffusion. However, higher relative humidity in the ventilation air hinders moisture diffusion, impeding surface moisture reduction and adversely affecting the drying process. These methods and findings offer theoretical support and references for designing and optimising drying systems. •The heat and moisture transfer are studied by computed tomography and COMSOL.•The pressure and temperature show a stratification phenomenon in airflow direction.•The moisture diffusion necessitates more drying time compared to heat transfer.•Higher air temperatures and velocity enhance heat transfer and moisture diffusion.•Lower relative humidity promotes moisture diffusion while may hinder grain heating.